Functionally distinct RNA polymerase binding sites in the phage Mu mom promoter region. - Balke, V (1992)
Transcription of the phage Mu com/mom operon is trans-activated by another phage gene product, C, a site-specific DNA binding protein. To gain insight into the mechanism by which C activates transcription, we carried out footprinting analyses of Escherichia coli RNA polymerase (= RNAP) binding to various com-lacZ fusion plasmids. KMnO4-sensitive sites (diagnostic of the melted regions in open-complexes) and DNase I-sensitive sites were located by primer-extension analysis. The results are summarized as follows: (i) in vivo, in the absence of C, RNAP bound in the wild-type (wt) promoter region at a site designated P2; in vitro DNase I-footprinting showed that P2 extends from -74 to -24 with respect to transcription initiation. This overlaps a known strong C-binding site (at -35 to -54). RNAP bound at P2 appeared to be in an open-complex, as evidenced by the presence of KMnO4-hypersensitive sites. (ii) In contrast, when C was present in vivo, RNAP bound in the wt promoter region at a different site, designated P1, located downstream and partially overlapping P2. RNAP bound at P1 also appeared to be in an open-complex, as evidenced by the presence of KMnO4-hypersensitive sites. (iii) Two C-independent mutants, which initiate transcription at the same position as the wt, were also analyzed. In vivo, in the absence of C, RNAP bound mutant tin7 (contains a T to G substitution at -14) predominantly at P1; in vitro DNase I-footprinting showed that P1 extends from -56 to +21. With mutant tin6 (a 63 base-pair deletion removing P2, as well as part of P1 and the C-binding site from -35 to -54), RNAP bound to P1 independent of C. We conclude that P1 is the 'functional' RNAP binding site for mom-transcription initiation, and that C activates transcription by promoting binding at P1, while blocking binding at P2.